2019
DOI: 10.1111/apps.12228
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Resilience: Managers’ Perceptions of Firm Performance Following M&As

Abstract: We study mergers and acquisitions (M&As), resilience and performance, identifying links between managers' perceptions of performance and resilience, using trans-national organisational-level survey evidence (N = 3,613) and follow up semi-structured in-depth interviews with managers involved in M&As and demerger. Drawing on the resilience and M&A literature, we identify reasons why employees in acquired firms may be less resilient in coping with the resultant changes than those of the acquirer and why this will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 108 publications
(139 reference statements)
0
5
0
Order By: Relevance
“…The importance of signals sent by entrepreneurs is intricately linked to how they are interpreted by the receiver. Male and female entrepreneurs seeking finance might be perceived differently (Croucher et al ., 2020; Greene et al ., 2001). Studies focusing on signalling theory, as well on gender congruity theory, have suggested that investors may have gendered perceptions and thus expect the entrepreneurs seeking funding to be male (Eddleston et al., 2016; Hughes et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of signals sent by entrepreneurs is intricately linked to how they are interpreted by the receiver. Male and female entrepreneurs seeking finance might be perceived differently (Croucher et al ., 2020; Greene et al ., 2001). Studies focusing on signalling theory, as well on gender congruity theory, have suggested that investors may have gendered perceptions and thus expect the entrepreneurs seeking funding to be male (Eddleston et al., 2016; Hughes et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Employee attitudes may also be affected by the strategic intent of M&As, especially regarding efficiency-oriented M&As that increase the likelihood of downsizing (Siegel & Simons, 2010). Negative attitudes towards M&As are more likely on the target firm side (Croucher et al, 2020), although it is possible for target firm employees to perceive acquisitions as opportunities, especially if target firm managers are responsive and promote the acquisition (Teerikangas, 2012). 1c.…”
Section: A Employee Characteristicsmentioning
confidence: 99%
“…Considerable attention was paid to challenges related to fostering employee resilience. It was revealed that employees often understood reinforcement practices in different ways than managers expected (Young, 2020;Glaister et al, 2020;Borekci et al, 2021;Chen and Zhang, 2021;Rodigues-Sanchez et al, 2021). The managerial principles of anticipating the future direction of activity were analyzed (Denyer, 2017;Beuren et al, 2020;Parnell et al, 2020;Wicker, 2021;Leta and Chan, 2021;Abdalla et al, 2021;Salas -Vallina et al, 2022) and the influence of various circumstances of uncertainty on organizational resilience were discussed (Santoro et al, 2020;Skoloudis et al, 2020;Low et al, 2021;Župerkienė et al, 2021).…”
Section: Introductionmentioning
confidence: 99%